MERANCANG LINGKUNGAN BELAJAR YANG POSITIF DAN PRODUKTIF: SISWA EFL MULTIKULTURAL DI PENDIDIKAN TINGGI DI UZBEKISTAN - Rimajon Sotlikova; Jimat Susilo (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2024)
The study explores the application of culturally responsive pedagogy, differentiated instruction, and active learning strategies to foster a positive and productive learning environment for English as a Foreign Language (EFL) learners in Uzbekistan. The data consisted of semi-structured interviews with Uzbek State World Languages University students, the National University of Uzbekistan, and Tashkent State Pedagogical University. This research aims to identify effective teaching practices that meet the diverse needs of students. The findings, the importance of integrating culturally relevant materials and activities to increase student engagement and cultural understanding in the field of EFL education. The study's results that combine culturally responsive teaching, differentiated instruction, and active learning can support the academic and social development of students from diverse cultural backgrounds. This approach enhances language proficiency and promotes mutual respect and cultural appreciation among students. The study concludes with practical recommendations for educators to implement these strategies effectively, thus contributing to a broader discourse on equitable and inclusive education in multicultural settings. These findings offer valuable implications for educators, policymakers, and researchers dedicated to improving EFL education for culturally and linguistically diverse student populations.